Comparative study of adenosine deaminase activity, insulin resistance and lipoprotein(a) among smokers and healthy non-smokers - Ramasamy, Ramesh; Murugaiyan, Sathish Babu; U., Arulkumaran; R., Sathiya; V., Kuzhandai Velu; Gopal, Niranjan (International Journal of Research in Medical Sciences, 2017)
Background: Adenosine deaminase also known as adenosine aminohydrolase involved in purine metabolism. Its primary function is development and maintenance of immune system. The main objective of the study was to estimate adenosine deaminase (ADA) enzyme and find its correlation with lipoprotein(a) and insulin resistance among smokers and healthy non-smokers. Methods: Fifty smokers and fifty healthy non-smokers were selected based on WHO definition. ADA, lipid profile and glucose was estimated on a fully automated analyser by IFCC approved methods and lipoprotein(a) was done by latex enhanced immune-turbidimetric assay method respectively. Results: After appropriate screening ADA activity and insulin was significantly elevated among smokers when compared with healthy non-smokers. A positive correlation was found between pack size of cigarette and ADA activity and also with Lp(a) respectively. In addition, there was no correlation between serum lipid profile and ADA activity. Conclusions: Adenosine deaminase activity was increased in patients in response to nicotine which is the key component of cigarette smoke. These findings indicate that nicotine and carbon monoxide can alter lipoprotein synthesis and also modify LDL to oxidized form which can lead to ischemic heart disease.